The Interview Times : Special edition | Buraxılış No.7 | Oktyabr, 2022 ﻿ - El Presidente; Şahməmmədli, Cavid; Kamanga, Nathan; Namazova, Fidan; Eyvazova, Fəridə; Əsgərova, Suğra; Duran, Alejandra Garcia; Ağalarzadə, Mahirə (ADA University, 2022)
2022 is the 10th anniversary of the "ADA BA2017 Class". Thus, the ADA life of this course began on October 1, 2012. For this reason, the October 2022 edition of "The Interview Times" newspaper is dedicated to the 10th anniversary of the "BA2017 Class".

In order to read full interview, click View/Open section below.
Keywords: ADA University--Newspaper.